Efficacy of blood plasma spectroscopy for early liver cancer diagnostics in obese patients - Hříbek, Petr; Vrtělka, Ondřej; Králová, Kateřina; Klasová, Johana; Fousková, Markéta; Habartová, Lucie; Kubíčková, Kristýna; Kupsa, Tomáš; Tůma, Tomáš; Setnička, Vladimír; Urbánek, Petr (Annals of hepatology, 2024)
INTRODUCTION AND OBJECTIVES: Hepatocellular carcinoma (HCC) represents one of the most common cancers worldwide. A considerable proportion of HCC is caused by cirrhosis related to metabolic dysfunction-associated steatohepatitis (MASH). Due to the increasing prevalence of metabolic syndrome, it is estimated that MASH-related HCC will become the most prevalent etiology of HCC. Currently, HCC screening is based on liver ultrasonography; however, the sensitivity of ultrasonography for early HCC stages in obese patients only reaches 23 %. To date, no studied biomarker shows sufficient efficacy for screening purposes. Nevertheless, the usage of spectroscopic methods offers a new perspective, as its potential use would provide cheap, fast analysis of samples such as blood plasma. MATERIAL AND METHODS: We employed a combination of conventional and chiroptical spectroscopic methods to study differences between the blood plasma of obese cirrhotic patients with and without HCC. We included 20 subjects with HCC and 17 without evidence of liver cancer, all of them with body mass index ≥ 30. RESULTS: Sensitivities and specificities reached values as follows: 0.780 and 0.905 for infrared spectroscopy, 0.700 and 0.767 for Raman spectroscopy, 0.840 and 0.743 for electronic circular dichroism, and 0.805 and 0.923 for Raman optical activity. The final combined classification model based on all spectroscopic methods reached a sensitivity of 0.810 and a specificity of 0.857, with the highest area under the receiver operating characteristic curve among all models (0.961). CONCLUSIONS: We suggest that this approach can be used effectively as a diagnostic tool in patients who are not examinable by liver ultrasonography. CLINICAL TRIAL REGISTRATION: NCT04221347.
Keywords: dospělí; Female; časná detekce nádoru; Liver Cirrhosis; hepatocelulární karcinom; Adult; ženské pohlaví; Predictive Value of Tests; Obesity; jaterní cirhóza; prediktivní hodnota testů; lidé; nádory jater; Carcinoma, Hepatocellular; studie případů a kontrol; Ramanova spektroskopie; ROC křivka; Liver Neoplasms; obezita; Male; nádorové biomarkery; Aged; Case-Control Studies; index tělesné hmotnosti; Spectrum Analysis, Raman; Early Detection of Cancer; Biomarkers, Tumor; lidé středního věku; senioři; mužské pohlaví; Body Mass Index; Middle Aged; ROC Curve; Humans